2013
DOI: 10.1097/scs.0b013e31827c8706
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Effect of Mesenchymal Stem Cells on Mandibular Distraction Osteogenesis

Abstract: Transplantation of mesenchymal stem cells promotes maturity of the distracted callus. The new experimental model, which allowed to test the mandible as a system by simulating in vivo loading conditions, revealed differences in the mechanical behavior of the halves of mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
0
26
0
3
Order By: Relevance
“…In both long bone [15]–[18] and mandibular DO studies [19][21], to date the most commonly used method of cell delivery is direct injection of MSCs carried by platelet rich plasma, saline or collagen gel. While an injection method sounds straightforward, the difficulty involved in delivering the cells to the desired locations of a closed subcutaneous bone site cannot be overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…In both long bone [15]–[18] and mandibular DO studies [19][21], to date the most commonly used method of cell delivery is direct injection of MSCs carried by platelet rich plasma, saline or collagen gel. While an injection method sounds straightforward, the difficulty involved in delivering the cells to the desired locations of a closed subcutaneous bone site cannot be overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of the sheep mandible to the human mandible consists of not only anatomic or macroscopic properties but also physiologic properties. 25,26 The physiologic similarities of the sheep mandible to the human mandible, in terms of distraction, have been revealed by Knabe et al 25 Growth factor expression after clinical mandibular DO in humans and its comparison with existing animal studies were reported by Knabe et al, 25 and the authors found that the expression pattern of growth factors secondary to human DO closely resembled those observed in the sheep model. This similarity was also mentioned in studies performed by Ploder et al 13 and Ayoub et al 22 Because of all these similarities, the sheep mandible model was selected in our study.…”
Section: Discussionmentioning
confidence: 72%
“…. Manual selection following the inclusion criteria resulted in a total of 19 studies as summarized in Table .…”
Section: Resultsmentioning
confidence: 99%